Pengaruh Cita Rasa dan Harga Terhadap Minat Beli Ulang Konsumen Pada Soto Ayam Pak Jo - Anggani, Mita Dwi (Jurnal Cendekia Manajemen (JCM), 2024)
Abstract This study aims to determine how the influence of the independent variables, namely taste and price on the dependent variable, namely repeat interest in consumers of Pak Jo's Chicken soup. This study uses quantitative methods by distributing questionnaires to obtain data. This study uses multiple linear regression tests, t tests, F tests, and coefficients of determination. with the help of SPSS 26. The sampling technique in this study used incidental sampling. The number of samples used in this study were 99 respondents. Based on the results of the study, it can be concluded that Taste partially has a positive and significant effect on Repurchase Interest, Price partially has a positive and significant effect on Repurchase Interest, Taste and Price simultaneously have a positive and significant effect on Repurchase Interest. This research is made so that companies can further improve various factors that can create repeated buying interest. Keywords: Taste, Price, and Repurchase Intention